Ultrasonography Monitoring of Trauma-Induced Heterotopic Ossification: Guidance for Rehabilitation Procedures - Wang, Qing; Zhang, Peizhen; Li, Pengdong; Song, Xiangfen; Hu, Huijing; Li, Xuan; Chen, Wufan; Wang, Xiaoyun (Frontiers in Neurology, 2018)
Traumatic injury is one of varying causes of heterotopic ossification (HO). After HO occurrence, rehabilitation training need alterations to avoid the aggravation of HO. Therefore, monitoring of HO development plays an important role in the rehabilitation procedure. The aims of this study are to evaluate the post-traumatic HO occurring at various joints, to describe the features of HO development in ultrasound images, and to provide a guidance for the orthopedist to make individualized rehabilitation therapy. Eight subjects with the post-traumatic HO were recruited in this study. The joint on the injured side was examined by plain radiography. The joint on the injured side and the corresponding site on the uninjured sides were scanned by ultrsonography. The HO tissues was segmented automatically using a semi-supervised segmentation algorithm. Then the HO tissues were evaluated in comparison with the corresponding region of the uninjured side. During the development stage of immature HO, ultrasonography was sensitive to observe the involved soft tissue and the calcification of HO. The characteristics of HO tissues in ultrasound image included the hyperechoic mass occasionally accompanied with acoustic shadow and the irregular muscular architecture. It was found that the mean greyscale value of HO was significantly higher (p＜0.001) than that of the uninjured side at the middle and late stages. During the development period of HO, the HO greyscale value gradually increased and the mean greyscale of value of mature HO was significantly higher (p＜0.05) than that of immature HO. According to the information of HO provided by ultrasound, the orthopedist properly adjusted the rehabilitation treatment. The results demonstrated that the visualization of HO using ultrasonography revealed the development of HO in the muscle tissues around the injured joints and thus provide a guidance for the orthopedist to make individualized rehabilitation therapy. Ultrasound could be a useful imaging modality for quantitative evaluation of HO during the rehabilitation of traumatic injury.